An Examination of Regional Policy Implications Pertaining to SME E‐Business Adoption in South‐East Wales1. (15th September 2015) - Thomas, Brychan; Miller, Christopher; Simmons, Geoff
Abstract : Regional policy frameworks need to focus on strengthening the ICT infrastructure, clarifying market rules to build user confidence, developing networks, facilitating ICT‐enabled clustering and infrastructure sharing.